Pertanggungjawaban Pidana Terhadap Pelaku Tindak Pidana Ransomware dalam Perspektif Peraturan Perundang-Undangan - Wahyuning Robbi, Suci; Hafrida, Hafrida; Monita, Yulia (Faculty of Law, Universitas Jambi, 2025)
Criminal liability for perpetrators of ransomware crimes is to determine whether or not a person who commits the crime can be held accountable for his actions. Perpetrators of ransomware crimes must fulfill the elements of criminal liability. Regulations on criminal liability for perpetrators of ransomware crimes can be guided by Article 27B paragraph (1) of the ITE Law, Article 30 paragraph (2) of the ITE Law, Article 32 paragraph (1) of the ITE Law, Article 368 paragraph (1) of the Criminal Code, and Article 67 paragraph (1) of the Personal Data Protection Law by imposing criminal sanctions as a form of criminal liability for ransomware crimes, but in the regulation of these articles there is still a lack of norms, where there are elements of ransomware that have not been fulfilled in these articles so that there are no articles that clearly regulate ransomware crimes. So it is difficult for perpetrators of ransomware crimes to be held criminally accountable, and there is no affirmation in these regulations so that this case is difficult to prove. Therefore, the form of criminal liability for perpetrators of criminal acts from the perspective of statutory regulations has not been realized. So that in imposing criminal sanctions on perpetrators of ransomware crimes, there is no article that is used clearly, making it difficult for perpetrators to be subject to this article in criminal responsibility. Abstrak Pertanggungjawaban pidana terhadap pelaku tindak pidana ransomware adalah untuk menentukan apakah seseorang yang melakukan perbuatan pidana tersebut dapat diminta pertanggungjawaban atau tidak atas tindakannya. Pelaku tindak pidana ransomware harus memenuhi unsur-unsur pertanggungjawaban pidana. Pengaturan tentang pertanggungjawaban pidana bagi pelaku tindak pidana ramsomware dapat berpedoman pada Pasal 27B ayat (1) UU ITE, Pasal 30 ayat (2) UU ITE, Pasal 32 ayat (1) UU ITE, Pasal 368 ayat (1) KUHP, dan Pasal 67 ayat (1) UU perlindungan data pribadi dengan menjatuhkan sanksi pidana sebagai bentuk pertanggungjawaban pidana atas tindak pidana ransomware, tetapi pada pengaturan pasal tersebut masih mengalami kekaburan norma , yang dimana terdapat unsur-unsur ransomware yang belum terpenuhi dalam pasal tersebutsehingga belum ada pasal yang mengatur secara jelas mengenai tindak pidana ransomware. Maka pelaku tindak pidana ransomware sulit untuk diminta pertanggungjawaban pidana, serta tidak ada penegasan dakam aturan tersebut sehingga kasus ini sulit di buktikan. Oleh karena itu, bentuk pertanggungjawaban pidana terhadap pelaku tindak pidana dalam perspektif peraturan perundang- undangan belum terwujud.